Decoy engineering of the receptor‐like cytoplasmic kinase StPBS1 to defend against virus infection in potato. (7th April 2022) - Bai, Runyao; Li, Huanhuan; Du, Wenjia; Niu, Niu; Li, Wenxia; Gao, Qican; Yao, Chongyang; Zhou, Zikai; Bao, Wenhua; Che, Mingjia; Zhao, Yongxiu; Zhou, Bin; et al.
Abstract: Potato virus Y (PVY) is an important pathogen of potato ( Solanum tuberosum ). Although the PBS1–RPS5 immune system is well documented in Arabidopsis thaliana, it has not been reported in potato. In Arabidopsis, the bacterial effector AvrPphB cleaves AtPBS1 to trigger an immune response. Here, we show that the AvrPphB‐triggered immune response is mediated by StPBS1, a close homologue of AtPBS1 in potato. However, downstream signalling of StPBS1 was mediated by unknown resistance (R) proteins other than potato orthologues of AtRPS5 and HvPBR1, which is important for HvPBS1 signalling in barley. Immune signalling of StPBS1 is mediated by the AvrPphB C‐terminal cleavage domain and an STKPQ motif, in contrast to AtPBS1‐mediated immunity in which both AvrPphB cleavage fragments and an SEMPH motif are essential. The cleavage sequence of AvrPphB in StPBS1 was replaced with that of the PVY NIa‐Pro protease to obtain StPBS1 NIa . StPBS1 NIa overexpression potato displayed stronger immunity to PVY infection than did the StPBS1 transgenic lines. StPBS1 NIa was cleaved at the expected target site by NIa‐Pro protease from PVY. Thus, we characterized the function of StPBS1 in potato immunity and provide a biotechnology control method for PVY via transformation of decoy‐engineered StPBS1 NIa . Abstract : The receptor‐like cytoplasmic kinase StPBS1 was decoy‐engineered to recognize NIa protease of potato virus Y, an important pathogen of potato, to trigger immunity and to provide a biotechnology control method for invading PVY.